Experimental Study of the Effect of Crude Palm Oil (Non-Newtonian Fluid) Viscosity on Increasing Flowrate Capacity - Bela Amelia; Amnur Akhyan (International ABEC, 2022)
: Crude Palm Oil's viscosity level is very influential in the distribution in palm oil mills. This research shows that the high temperature will cause the viscosity to decrease. The force given to Crude Palm Oil can also reduce its viscosity levels. This proves that Crude Palm Oil is a Non-Newtonian fluid. This test shows that Crude Palm Oil with a temperature below 60°C has a discharge that is still changing from the first minute to the third minute. Meanwhile, Crude Palm Oil with a temperature above 60°C has a discharge that does not change after the first minute. From this, it can be concluded that 60°C is the best temperature for palm oil mills in the distribution of Crude Palm Oil.